Pemahaman Tentang Kebenaran dan Keadilan Dalam Filsafat Kristen - Helvin Murni Gulo; Mozes Lawalata (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This article discusses the concept of God's truth and justice manifested in justice, truth and honesty. In this case, understanding the truth and justice of God is real and concrete in human life. The results of this study show that God's righteousness is reflected in acts of justice and honesty which have implications for human attitudes and actions horizontally, especially for believers who believe in Christ.